G531(P) Effect on cardiorespiratory function in term and preterm infants sitting in a car safety seat, in a simulated moving vehicle (pilot study). (7th April 2014) - Arya, R; Williams, G; Kilonback, A; Toward, M; Griffin, M; Fleming, P; Blair, P
Abstract : Introduction: The AAP recommends preterm infants undergo a "car seat challenge" before discharge, to observe for any differences in cardiorespiratory function whilst seated in a car seat compared to lying flat in a cot. The infant can be discharged if there is no compromise. This static (30°) challenge does not take into account the more vertical positioning of the seat or effects of vibration when it is secured in a moving vehicle. Aim: To investigate the effect of vibration, mimicking that experienced in a moving car, on cardio-respiratory function, compared to the standard challenge. Methods: A novel simulator was designed to represent the vibrations felt in a rear facing car seat during a normal urban cycle. 40 term & preterm babies, ready for discharge after birth, were recruited. The babies were their own control. Observations of heart & respiratory rates, saturation & end tidal CO2 levels were recorded flat in a cot, static in the seat (30°) & simulator (40°) & during vibration (motion). Results: 19 term & 21 preterm infants were tested; 22 were male (55%). Gestation range was 25+2 weeks to 41+5 weeks (median 35+5). Median birthweight was 2.5 kg (range 0.8 kg to 4.8 kg). Age at testing was 1 to 65 days (median 13 days). There were no significant differences in outcome variables for infants in the cot & 30° position. However, compared to rest, in the static 40° position infants had significantly faster heartbeats, lower oxygen saturation & higher respiratory rates. When in motion these differences persisted & the number of desaturations below 85% were significantly higher. Conclusions: Testing all infants at 30° would suggest they could travel. However both term & preterm babies showed signs of cardio-respiratory distress in the 40° position with a significant increase in profound desaturations during motion, which were underestimated by the standard challenge. A larger study is required to confirm these results. This may lead to revision of the current car seat challenge or the design of infant car seats.